(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2012)
This study attempts to highlights on the evaluation of performance efficiency for Investments in both National & Iraqi Insurance companies for the years 2001-2010 and their importance on those companies and the economy of the country in order to find out the investment areas and to compare between investment activity and its revenues as well as to compare performance of both companies in investment field. The study was based on annual reports and balance sheets of both companies. In many chapters, this study dealt with theoretical and practical aspects of the investments and its revenues. Key hypothesis was based on this study, including four parts of Sub hypotheses about (statistical effective relationship between the amount of investment and achieved revenues). The study found many conclusions, including: National Insurance Company and Iraqi Insurance Company do not have sufficient flexibility to expand the investment projects because they are state-owned companies and subject to state laws and regulations.Investments include risks such as currency exchange rates, risks of falling stocks and bonds, risks of fluctuating prices of real estate investments, risks of changing interest rates and risks of repayment of borrowers.Insurance companies adopt diversity of investments, which is considered as one of the important principles that governing investments in financial institutions in general and in insurance companies in particular, this leads to improve the profitability and reduce risks in addition to providing high liquidity throughout the year.The most important recommendations reached by the research are.Follow up scientific method to take proper decisions about investment in the presence of many available alternatives through the use of modern scientific methods in comparison between those alternatives.Develop section for risk management in order to prevent and reduce the potential material loss, then reduction of uncertainty through the main function of disclosure risk first, and to analyze and control those risks and reduce associated costs and, second, choose the best means to address these risks by developing a system, identify early warning indicators of risk and the possibility of control any risk may occur and how to get around it.